STUDENTS SCIENCE MISCONCEPTIONS CONCERNING THE STATE CHANGES OF WATER AND THEIR REMEDIATION USING THREE DIFFERENT LEARNING MODELS IN ELEMENTARY SCHOOL - Taufiq, M.; Hindarto, N.; Khumaedi, - (Jurusan Fisika, Fakultas Matematika dan Ilmu Pengetahuan Alam, Universitas Negeri Semarang, 2011)
Secara umum, kesalahpahaman yang dialami oleh mahasiswa dapat menyebabkan kesulitan dalam penelitian, sementara anakanakmemiliki kesadaran mereka sendiri. Tingkat kesalahpahaman yang dialami oleh siswa juga tidak sama, dalam kasus inisesuatu mengalami kesalahpahaman pengalaman tingkat tinggi, menengah, dan rendah. Untuk alasan itu, siswa memerlukanmodel pembelajaran yang tepat untuk masing-masing tingkat kesalahpahaman yang dialami untuk membuat studi menjadibermakna. Dalam makalah ini, peneliti mengeksplorasi informasi tentang; (1) tingkat kesalahpahaman ilmu siswa tentangperubahan wujud dari air, dan (2) model pembelajaran yang paling efektif untuk mengatasi kesalahpahaman siswa mengenaiperubahan wujud air. Model pembelajaran tiga dalam penelitian ini adalah: siklus belajar, penyelidikan dipandu, dan model konseppemetaan. Metode yang diterapkan dalam penelitian ini adalah wawancara klinis dan pretest-posttest. Informasi yangdikumpulkan dianalisis secara kuantitatif dengan percobaan uji ANOVA dan keuntungan rata-rata normal dihitung untuk setiapkelompok percobaan.ÃÂ In general, misconceptions experienced by student could cause difficulties in study, meanwhile children have their own sense.Level of misconceptions experienced by student also unequal, in this case something experiences high level misconceptions,medium, and low. For that reason, student requires correct learning model for each level of misconception experienced to make thestudy become meaningful. In this paper, the researcher explored information about; (1) the level of science misconceptions of thestudent concerning the state changes of water, and (2) the most effective learning model to remedy students misconceptionsconcerning the state changes of water. The three learning models in this research are: learning cycle, guided inquiry, and conceptmapping model. The method applied in this research is the clinical interview and pretest-posttest. The information collected wasanalyzed in experiment quantitative manner by anova test and average normalized gains were calculated for each experimentgroup.Keywords: science misconceptions; learning cycle; guided inquiry; concept mapping